Ellagic Acid Administration Negated the Development of Streptozotocin-Induced Memory Deficit in Rats - Bansal, Nitin; Yadav, Pushplata; Kumar, Manish (Drug Research, 2017)
Rampant production of pro-oxidants and inadequate antioxidant availability in brain exert oxidative stress, which in synergism with impaired glucose metabolism and inflammation leads to neurodegeneration and cognitive deficits. Ellagic acid (EGA) is a phenolic compound present in various fruits and is reported to possess robust antioxidant and anti-inflammatory properties. The present study investigated the effect of EGA administration on streptozotocin (STZ) induced dementia in rats. Bilateral intracerebroventricle (ICV) injection of STZ (3 mg/kg) was given to Wistar rats (200 g) on day 1 and 3. EGA (17.5 and 35 mg/kg) was administered orally to rats for 28 days daily. The spatial memory of rats was quantified by using Morris water maze and elevated plus maze. Brain TBARS, GSH and TNF-α were also measured. Administration of EGA prevented the induction of STZ-ICV triggered cognitive deficits as evident by a significant (p<0.05) reduction in mean escape latency during acquisition trial and increased (p<0.05) time spent in target quadrant during retrieval trial in Morris water maze test, and reduction (p<0.05) in transfer latency in elevated plus maze test. Furthermore, both the doses of EGA attenuated STZ-ICV induced rise in brain TBARS as well as TNF-α and simultaneously enhanced the GSH content. Thus, EGA ameliorated STZ-induced dementia by probably restoring the balance between cellular pro-oxidants and anti-oxidants in brain of rats.
Keywords: dementia; ellagic acid; oxidative stress; inflammation; memory